2016
DOI: 10.2169/internalmedicine.55.7250
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax Associated with Chronic Lymphocytic Leukemia

Abstract: An 80-year-old man who had suffered from chronic lymphocytic leukemia (CLL) and achieved complete remission was admitted to our hospital due to right pleural effusion. Thoracentesis revealed that the effusion was chyle. Lymphoscintigraphy showed an obstruction of the thoracic duct below the sternum. CD45-gated flow cytometry of the pleural effusion showed elevated numbers of CD5- and CD23-positive lymphocytes and a high serum level of soluble interleukin-2 receptor. These results suggested that the chylothorax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…However, as more cases were described, it became apparent that many of the cases in which chylothorax was seen in CLL, mediastinal lymphadenopathy large enough to obstruct flow was not present. Later reports described alternative theories that, aside from potential obstruction from mediastinal lymphadenopathy, the increased number of abnormal lymphocytes present in CLL leads to sludging in the lymphatic system and a pseudo-obstruction within the lymphatic system [9]. This theory is supported by the fact that in a literature review of the prior reported cases, almost all patients had a recent history of rapid doubling in leukocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…However, as more cases were described, it became apparent that many of the cases in which chylothorax was seen in CLL, mediastinal lymphadenopathy large enough to obstruct flow was not present. Later reports described alternative theories that, aside from potential obstruction from mediastinal lymphadenopathy, the increased number of abnormal lymphocytes present in CLL leads to sludging in the lymphatic system and a pseudo-obstruction within the lymphatic system [9]. This theory is supported by the fact that in a literature review of the prior reported cases, almost all patients had a recent history of rapid doubling in leukocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rarity of both chylothorax and chylopericardium [5][6][7][8][9][10] , the necessary and sufficient anatomic and physiologic circumstances for the development of such chylous effusions have not been defined. Thoracic duct ligation studies in dogs 11 demonstrated recruitment of lymphaticovenous connections with the potential for flow of chyle into systemic veins despite the thoracic duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Etiologies of Chylothorax can be broadly divided into traumatic, malignancy, miscellaneous and idiopathic. 1 , 3 The thoracic duct typically arises from the cisterna chyli and enters the chest cavity through the aortic hiatus. It ascends through the chest to the right of the vertebral column and crosses to the left at the level of the carina and then drains in the left jugulo-subclavian vein junction.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral chylothorax caused by chronic lymphocytic leukemia (CLL) has been rarely reported in the literature. 1 Lymphoma accounts for around 70% of cases due to malignancy. 2 Bilateral chylothorax caused by CLL has been rarely reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation